Avaliação experimental do coeficiente de transferência de calor suspensão-parede em regime de leito fluidizado borbulhante monitorado pelo método da frequência central gaussiana - Turini, Bruno Alves Figueroa (2017)
Bubbling fluidized beds (BFBs) are well known as efficient systems for thermal energy transfer in several industrial applications. Although many works have already pointed out the performance features of gas-solid BFB heat exchangers, more data about the design and operation of these devices are needed when using pressure fluctuation techniques for the hydrodynamics control. Considering this gap, the procedure for the design of a jacket-type heat exchanger placed in a bench scale bubbling fluidized bed column and the experimental assessment of its bed-to-wall heat transfer coefficient under several operating conditions are presented here. As a guarantee for operating the system under a bubbling fluidization regime, as well as in conditions close to the minimum fluidization, the central Gaussian frequency method is applied. By using this method, it is possible to identify the defluidization phenomenon from pressure fluctuations measurements. The experimental information was analyzed assuming uniform heat flux (solution of second type) or uniform temperature (solution of third type) in the inner wall of the water jacket. Initial tests were performed at fluidization velocity uo/umf ratio equal to 4, involving water mass flow rates in the range of 1.83 ± 0.01 kg/h to 4.46 ± 0.02 kg/h. Other experimental tests, this time involving water mass flow rate kept constant at 3.62 ± 0.01 kg/h, were carried out with particles of 194 and 359 μm in Sauter mean diameter and with fluidization air fed in uo/umf ratios changing from 0.5 to 4.0. In all tests of this study, the water flow regime in the annular region of the heat exchanger was identified as laminar and thermally developing. Results indicated that the bed-to-wall heat transfer coefficient varies in the range of 169.93 ± 7.52 W/m²K to 353.28 ± 29.78 W/m²K for the second type solution and from 191.54 ± 8.55 W/m²K to 468.43 ± 39.27 W/m²K for the third type solution, when using bed temperatures of 50 °C and 70 °C. The analysis of these results confirms that by using the finer particle or the higher bed temperature, the value of the bed-to-wall heat transfer coefficient tends to increase. In addition, results suggested that a maximum value of the bed-to-wall heat transfer coefficient can be obtained in the range of uo/umf ratio tested, which is in agree with previous works.